Location Selection of Surabaya Landfill using Integration of the PROMETHEE and the AHP Methods - Nova Indah Saragih; Peri Turnip (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2026)
Surabaya is the second-largest city in Indonesia. Like other major cities, Surabaya faces waste problems. The amount of waste produced by Surabaya residents has increased annually. This is partly due to the growing population. Currently, municipal waste management is still centralized in the Benowo Landfill. Owing to the increasing amount of waste and limited land available at the Benowo Landfill, a new landfill is needed. The selection of a landfill site is a complex problem because the selection criteria are multiple and conflicting with one another. The method used in this study is an integration of the PROMETHEE and AHP methods. The two MCDM methods were used to complement each other, and the weaknesses of one method were corrected by utilizing the strengths of the other, resulting in a better solution. This study aims to determine the location of a new landfill in Surabaya using the integration of the PROMETHEE and AHP methods. Based on the data processing that has been done, it is known that the new landfill location is in the Rungkut District.